Fostering The Love Of Arabic Language From An Early Age Through Play and Song-Based Learning In Islamic Early Childhood Education - Laili Mas Ulliyah Hasan; Izzah Nur Hudzriyah Hasan (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2025)
This community service project aims to foster early childhood interest and love for the Arabic language through play and song-based learning in Islamic early childhood education. The program was conducted with teachers and children at TKM Al-Asy’ari Sidoarjo, emphasizing joyful, interactive, and spiritually enriched learning experiences. The methods involved teacher mentoring, demonstration of Arabic songs, and implementation of play-based activities integrating basic Arabic vocabulary. Observation and interviews were used to evaluate children’s engagement, linguistic responses, and enthusiasm. The results showed a significant improvement in children’s motivation, memory of Arabic words, and participation during learning sessions. Teachers also reported increased confidence in applying creative Arabic teaching strategies. This study highlights the importance of integrating emotional, cultural, and spiritual elements in Arabic learning from an early age to build positive language attitudes and lay the foundation for future proficiency.